Optical Characterization of Major Compounds in Different Types of Commercial Olive Oil Using Photoluminescence Method. (2017) - Sena, Adhika Widya; Isnaeni,; Juliastuti, Endang
Abstract: Olive oil is a vital component in Mediterranean diet which is highly recognized for its health benefits, including but not limited to improving cardiometabolic markers, reducing incidence of neurodegenerative diseases and boosting cognitive performance. Despite the fact that olive oil has been widely used across the globe, the existing research is still focused on extra virgin olive oil per se, ignoring the fact that other olive oil types (such as classic and extra light) are also commonly used in our society. Moreover, most research still used long-procedure chemical methods to examine olive oil, only very littleresearchused an optical approach. In this study, we identified the major compounds in 3 types of commercial olive oil (classic, extra virgin and extra light) from different brands using photoluminescence method. A 355 nm Nd:YAG laser was used to trigger emissions from the olive oil sample which were then analyzed using a spectrophotometer. We managed to identify 4 oxidation products, 2 Vitamin E compounds and 2 chlorophyll compounds. The results from deconvolution using a Lorentzian profile showed that each olive oil type has a unique compounds proportion with chlorophyll as the most dominant substance. The composition consistency of each brand also varies, inferring different qualities between commercial olive oil products. Finally, we discussed the benefits of deconvolution and photoluminescence methods to characterize major compounds in different types of commercial olive oil. In conclusion, photoluminescence is a valid optical characterization method to characterize the compounds in different types of olive oil.